Dominant role of Atlantic multidecadal oscillation in the tipping point of maximum and minimum temperatures over inner East Asia. (14th December 2022) - Guo, Shuyang; Guan, Xiaodan; Gu, Tonghui; Shen, Xiaohan
Abstract: Despite unprecedented heatwave events reported in the past two decades over inner East Asia, the maximum and minimum temperatures of Tmax and Tmin do not always exhibit continuous increasing. After drastic increases in Tmax and Tmin appeared over inner East Asia from 1982, a decreasing trend occurred around 1998, which was closely associated with the Atlantic multidecadal oscillation (AMO). During 1950–2014, the correlation between Tmax (Tmin) and AMO at the decadal time scale reached 0.70 (0.83); and 65% (79%) variance of the decadal variability in Tmax (Tmin) was explained by the AMO and three other classic oceanic modes; the contribution of the AMO was up to 82% (91%) in the decadal modulated oscillation. The declines of Tmin and Tmax synchronized with the downward swing of the AMO since the late‐1990 s, which was because the AMO could affect the vertical motion and wind anomalies of inner East Asia through the cyclonic‐anticyclonic teleconnection wave train in the mid‐latitudes of the Northern Hemisphere. The results of composite analysis show that during the positive phase of the AMO, a local ascending motion was enhanced over inner East Asia and a large‐scale abnormal high was found north of East Asia in favour of cold air intrusion. Meanwhile, the start of growing season was delayed by the positive phase of the AMO over the northern part of inner East Asia due to the high sensitivity of spring phenology to the Tmin controlled by the AMO. Abstract : Inner East Asia experienced noticeable warming and unusual cooling during 1982–2014. The declines of Tmin and Tmax synchronized with the downward swing of the Atlantic multidecadal oscillation (AMO) since the late‐1990s, which was because the AMO could affect the vertical motion and wind anomalies of inner East Asia through the cyclonic‐anticyclonic teleconnection wave train in the mid‐latitudes of the Northern Hemisphere. The effect of AMO on Inner East Asia resulted in the opposite phase of spring phenological change. In response to the regional cooling in the warm AMO phase, the delay of the start of growing season was found in northern inner East Asia.